Clinical Cases in Hepatology - Bergasa, Nora V.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2022)
This book provides a comprehensive resource for clinical hepatology. It details the systematic approach to patients with liver disease in outpatient and inpatient medical settings. A variety of case studies in hepatology including chronic viral hepatitis, and metabolic, autoimmune, and alcohol related liver disease are presented. The book enables the reader to develop a thorough understanding of the clinical presentation, natural history, epidemiology, genetics, and therapeutic options for the liver diseases that clinicians must recognize and manage from the first encounter with the patient through the years of follow up. Clinical Cases in Hepatology systematically describes the approach to a patient with liver disease and is a valuable source for all medical professionals and trainees who care for these patients or are seeking a detailed reference guide to developing their knowledge in the rapidly expanding field of hepatology.
Acute hepatitis (e.g. viral, drug-induced) -- Primary biliary cirrhosis -- Liver disease secondary to alcohol abuse -- Non-alcoholic fatty liver disease -- Hepatic manifestations of sepsis -- Autoimmune hepatitis -- Cholestasis of pregnancy -- Complications of cirrhosis (e.g. portal hypertension, ascites, hepatic encephalopathy) -- Ischemic hepatitis -- AIDS and liver disease. .
Keywords: Internal medicine; Internal Medicine; Liver Diseases